3D automatic quantification applied to optically sectioned images to improve microscopy analysis - Diaz-Zamboni, JE; Adur, JF; Vicente, N; Fiorucci, MP; Izaguirre, MF; Casco, VH (European Journal of Histochemistry, 2009)
New fluorescence microscopy techniques, such as confocal or digital deconvolution microscopy, allow to easily obtain three-dimensional (3D) information from specimens. However, there are few 3D quantification tools that allow extracting information of these volumes. Therefore, the amount of information acquired by these techniques is difficult to manipulate and analyze manually. The present study describes a model-based method, which for the first time shows 3D visualization and quantification of fluorescent apoptotic body signals, from optical serial sections of porcine hepatocyte spheroids correlating them to their morphological structures. The method consists on an algorithm that counts apoptotic bodies in a spheroid structure and extracts information from them, such as their centroids in cartesian and radial coordinates, relative to the spheroid centre, and their integrated intensity. 3D visualization of the extracted information, allowed us to quantify the distribution of apoptotic bodies in three different zones of the spheroid.